The Image of Iceland and the Competitiveness of Saga Matkat - Kotimäki, Neea; Syrjä, Emma (2019)
In the 21st century traveling is no longer just a luxury for upper class citizens. With the increase in disposable income, leisure travel has become more easily accessible and attractive, and the Finnish tourist market is growing as a consequence. Therefore, there’s more competition in the industry and standing out is essential for both the agencies and the destinations. The research study focuses on the strengths and weaknesses of the Finnish travel agency Saga Matkat in the tourism field as well as the destination image of their main product Iceland. The objectives are to provide the agency knowledge of their advantages and disadvantages compared to their direct competitors and help them understand what kind of image Finnish tourists have of Iceland as a destination. This information can be further used in operations management. The theoretical framework of the study consists of introduction of the commissioner and their competitors, description of Iceland as a tourism destination as well as information about the Finnish tourist market presented through statistics. A mix-methods online survey was implemented to gather data. The data analysis was based on the answers of 155 participants. Additionally, the overall performance of Saga Matkat was studied using the data from the online survey supported with the competitive analysis and the SWOT analysis. The key findings of the study show that Iceland has a rather clearly defined image which is extremely similar to the image that Finnish tourists have of it. Furthermore, participants gave rather positive feedback of all the studied aspects regarding Saga Matkat. Conversely, the data showed no direct connection with the customer satisfaction and loyalty to Saga Matkat. This could be one option for possible future research for the company.